2019
DOI: 10.1073/pnas.1915389116
|View full text |Cite
|
Sign up to set email alerts
|

Self-renewing endometrial epithelial organoids of the human uterus

Abstract: The human endometrium is essential in providing the site for implantation and maintaining the growth and survival of the conceptus. An unreceptive endometrium and disrupted maternal−conceptus interactions can cause infertility due to pregnancy loss or later pregnancy complications. Despite this, the role of uterine glands in first trimester human pregnancy is little understood. An established organoid protocol was used to generate and comprehensively analyze 3-dimensional endometrial epithelial organoid (EEO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 78 publications
7
134
0
2
Order By: Relevance
“…It is unclear whether the exit strategy depends on the organization of polarized epithelial cell, cell-type specific responses, or serovar-specific functions. Because EMOs are comprised of a multiple epithelial subtypes (Fitzgerald et al, 2019), this model can be used to identify cell type-specific responses to infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the exit strategy depends on the organization of polarized epithelial cell, cell-type specific responses, or serovar-specific functions. Because EMOs are comprised of a multiple epithelial subtypes (Fitzgerald et al, 2019), this model can be used to identify cell type-specific responses to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have demonstrated that endometrial organoid cultures can be used to achieve the complexity of organ structures to a considerable degree through cellular self-assembly and can be used as preclinical models to study the physiology and pathology of human endometrium [17][18][19][20][21][22][23][24], these models do not fully recapitulate the regulatory mechanisms of endometrium in vivo. Herein with the use of full thickness endometrial tissue slice cultures we developed a unique model that dramatically enhances endometrial tissue viability and recapitulates the zone-specific changes seen in normal physiological conditions of endometrium [52][53][54].…”
Section: Induction Of Glandular Remodeling and Decidualization In Endmentioning
confidence: 99%
“…Recently, the development of 3D organoid cultures has gained attention as a powerful tool to study endometrial remodeling [17][18][19][20][21][22][23][24]. These cultures exploit the self-organization ability of endometrial cell types that reproduce many aspects of the phenotypical characteristics of endometrium [17][18][19][20][21][22][23][24]. The flexibility, reliability and reproducibility of organoid cultures derived from human endometrial cell types have largely helped to overcome the obstacle due to lack of animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Fitzgerald et al. combined organoids with bulk RNA-sequencing and single-cell RNA-sequencing (scRNA-seq) to establish a high-resolution gene expression atlas of EOs [ 21 ]. They expounded how EOs respond to reproductive hormones and found that the organoid was heterogeneous, embracing specific subpopulations of cells that were hormone responsive, including stem cells [ 21 ].…”
Section: Eos Culture Came From Mouse/human Endometriummentioning
confidence: 99%
“…and Fitzgerald et al. further studied the characteristics of human EOs [ 20 , 21 ], involving organoids from normal and abnormal endometrium. These researches described the specific composition of the EOs culture medium, the phenotypic (typical surface markers and structures) and genetic characteristics, and the responsiveness to hormones, and there were several similarities and differences in these studies.…”
Section: Introductionmentioning
confidence: 99%